Высокий уровень социально-правового мышления как фактор противодействия коррупции в судебной системе - Омрали, Ж.О. (Изд-во КарГУ, 2010)
Мақалада жемқорлыққа қарсы ықпал ететін факторлар қарастырылған. Сонымен қатар соттар жұмысын жақсарту, шет мемлекеттердің сот саласындағы жетістіктері туралы айтылған. The factor counteracting bribery are considered in this article. The issues of factors influencing the operation of courts and improvement of their work and also the achievements of foreign countries in judicial sphere are considered.